Dressing Judeans and Christians in antiquity - Upson-Saia, Kristi, 1974-; Daniel-Hughes, Carly, 1974-; Batten, Alicia J. (Burlington, VT : Ashgate, 2014)
"This volume aims to understand religious aspects of dress in the ancient world by examining a diverse range of religious sources, including literature, art, performance, coinage, economic markets, and memories. Contributors demonstrate how dress developed as a topos within Judean and Christian rhetoric, symbolism, and performance, and show how religious meanings were entangled with other social logics, revealing the many layers of meaning attached to ancient dress, as well as the extent to which dress was implicated in numerous domains of religious life"--
Includes bibliographical references and index.
Description based on print version record.
Keywords: Clothing and dress -- Religious aspects -- Judaism; Rabbinical literature -- History and criticism; Clothing and dress -- Religious aspects -- Christianity; RELIGION / Christian Life / General; Electronic books